FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PELAKSANAAN PERILAKU HIDUP BERSIH DAN SEHAT OLEH GURU UKS SEKOLAH DASAR DI KECAMATAN BANYUMANIK KOTA SEMARANG - Debora M. Siahaan; VG. Tinuk Istiarti; Bagoes Widjanarko (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
72% the teacher UKS in the city of Semarang had a low performance in their work. Implementation of PHBS by UKS teacher in District Banyumanik Semarang Ciy there was smoke in the school environment, supervision school canteen has not gone well, wash hands with soap at no links to the school. In 2015 ISPA is still high case, which is equal to 5521, 1100 and diarrhea of dental caries by 1281. Descriptive analytic method with cross sectional approach.Samples were taken by the method of total population of 38 people.Data analysis using chi-square test (significance level 0.05) in univariate and bivariate analysis. Respondents who was implementation of clean and healthy behavior are 52.6% good and 42.4% poor. Test Statistic shows the relationship between knowledges with the implementation of PHBs in school (pvalue=0,037). While the different result indicate there is never an association between attitudes (pvalue=0.89), the availability of facilities (pvalue=0.74), the availability of funds (pvalue=1.00), the support of health workers (pvalue=1.00), the support headmaster (pvalue=0.67) and the school regulations (pvalue=0.35) with the implementation of PHBS in school. For health worker in District Banyumanik can do an evaluation of training and guidance for teachers UKS for the implementation of PHBS in school more leverage.